(untitled) (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2025)
The ongoing decline in new student enrollment has placed private schools in Indonesia under increasing competitive pressure, particularly in relation to public schools and emerging alternative education providers. Despite this urgency, existing studies have not offered a consolidated analytical overview of how private schools strategically respond to these challenges. To address this gap, the present study conducts a systematic literature review restricted to peer-reviewed publications released between 2019 and 2025. Using predefined inclusion and exclusion criteria, a total of 12 relevant articles were identified from Scopus, Google Scholar, ERIC, and DOAJ, all of which specifically discuss strategic management and competitive practices within Indonesian private education. The thematic analysis reveals three dominant strategic patterns. First, differentiation strategies, including academic quality enhancement, teacher capacity building, and flagship program innovation, remain the most widely employed response to enrollment decline. Second, marketing and communication strategies, particularly digital branding, social media campaigns, and parent-centered communication models, have grown significantly as schools adapt to shifts in information-seeking behavior among prospective parents. Third, partnership and collaboration strategies, involving community outreach, industry linkages, and cooperation with religious or higher education institutions, function as complementary supports that strengthen institutional credibility. These findings underscore that strategic effectiveness in Indonesian private schools depends on the alignment between internal value propositions and the needs, expectations, and sociocultural dynamics of local communities. By synthesizing recent evidence into a structured thematic framework, this study provides a scientific foundation for private school leaders seeking to design evidence-based and context-responsive competitive strategies.